Acupuncture Management of Right Upper Abdominal Pain in Cholecystitis: A Case Study - Tri Ardani; Ikhwan Abdullah; Mayang Wulandari; Leny Candra Kurniawan (CV. Inara, 2026)
Right-sided abdominal pain caused by gallbladder inflammation (cholecystitis) is a common clinical condition that can significantly affect patients’ quality of life. Conventional management generally focuses on pharmacological therapy and surgical intervention, but these approaches may present limitations such as adverse effects and high medical costs. Therefore, complementary therapeutic approaches such as acupuncture have gained increasing attention as potential supportive treatments. This study aimed to describe the implementation and clinical outcomes of acupuncture care in reducing right-sided abdominal pain in a patient with cholecystitis treated at a therapy center in Banjarmasin. The research employed a qualitative case study design involving a 45-year-old female patient diagnosed with cholecystitis. Data were collected using a structured client data sheet based on the Traditional Chinese Medicine (TCM) diagnostic framework, including observation (Wang), listening and smelling (Wen), inquiry (Wen), and palpation (Qie). The participant received six acupuncture therapy sessions over a one-week period. Data analysis was conducted descriptively by comparing clinical findings before and after treatment. The results showed significant improvement in both subjective complaints and objective clinical indicators. The patient initially presented with severe right upper abdominal pain accompanied by nausea, decreased appetite, bitter taste in the mouth, and radiating pain to the scapula. After six therapy sessions, the main complaint of abdominal pain disappeared, accompanying symptoms decreased markedly, and physical examination findings improved. Ultrasonography also indicated the disappearance of previously detected gallstones. These findings suggest that acupuncture therapy may contribute to symptom reduction and functional improvement in patients with cholecystitis.